Soybean processing effects on the performance, carcass traits, and blood metabolites of broiler chickens - LEHMALI, IRAJ FATHI; JAFARI, MOHAMMAD ALI (The Indian Journal of Animal Sciences, 2021)
Processing methods are used to increase the nutritional value of soybean. The purpose of this research was to study the effect of different processing methods of soybean on performance, carcass traits, and blood metabolites of Ross broiler chickens. A factorial experiment was used in the form of a completely random design using 600 male Ross 308 broiler chickens for 42 days (in 3 feeding phases: starter, grower, and finisher). The experimental factors included the 2 soybean varieties (Katol and Caspian) and 4 processing methods (unprocessed, extruded, thermal, and gamma radiation). Data were measured and analyzed with the Lsmeans procedure by SAS package. Processing methods had a significant effect on the feed conversion ratio (FCR) at the starter and finisher phase. Soybean varieties had a significant effect on the FCR at the whole phase. Interaction of processing methods and soybean variety had a significant effect on the FCR at the finisher and whole phase. Processing methods had a significant effect on the albumin. Soybean varieties, processing methods and interaction of them had a significant effect on the phosphorus. Interaction of processing methods and soybean varieties had a significant effect on the live weight, thigh, wings, pancreas weight, uric acid, and Alkaline phosphatase (ALP). Results showed that extruded and thermal methods are the most suitable for soybean processing.